TINJAUAN YURIDIS EMPIRIS TERHADAP REKLAME YANG MELANGGAR SYARIAT ISLAM BERDASARKAN QANUN KABUPATEN ACEH BARAT NOMOR 3 TAHUN 2021 TENTANG KETENTERAMAN MASYARAKAT DAN KETERTIBAN UMUM DI KECAMATAN JOHAN PAHLAWAN - Cut Bella Roza; Nouvan Moulia (Jurist Argumentum: Pemikiran Intelektual Hukum, 2026)
This study examines the implementation of West Aceh Regency Qanun Number 3 of 2021 concerning Public Peace and Order, specifically Article 45 letter i, which prohibits advertisement billboards (reklame) from displaying content that violates Islamic law. Despite the existing regulation, violations persist among beauty salons in the Johan Pahlawan sub-district, where promotional materials frequently display women's aurat, contrary to local socio-religious norms. The objective of this research is to analyze the implementation of the aforementioned Qanun and identify the underlying obstacle factors hindering its enforcement. This research employs an empirical juridical method. Primary data were collected through field interviews with salon owners, customers, and key government officials, including representatives from the Civil Service Police Unit and Wilayatul Hisbah (Satpol PP and WH) and the Investment and One-Stop Integrated Services Agency (DPMPTSP). The collected data were analyzed using a qualitative descriptive approach. The results indicate that the implementation of the Qanun remains ineffective. This is primarily characterized by suboptimal inter-agency coordination, a reactive rather than preventive approach to law enforcement, and an absence of direct supervision following the issuance of business permits. Furthermore, the implementation has not fully aligned with the principles of Good Governance, particularly regarding transparency and public legal education. The primary obstacles lie in the discrepancy between the legal structure and legal culture. While the legal substance is clear, structural operational limitations and a profound lack of legal awareness among business owners—exacerbated by modern visual normalization and inadequate socialization—impede compliance. The study concludes that a transformational approach, shifting from repressive enforcement to educative, persuasive, and participative strategies, is essential to foster genuine social awareness and legal compliance.